Endoscopic Orientation of the Parasellar Region in Sphenoid Sinus with Ill-Defined Bony Landmarks: An Anatomic Study - Amin, Sameh M. (Thieme Medical Publishers, 2010)
The sphenoid bony landmarks are important for endoscopic orientation in skull base surgery but show a wide range of variations. We aimed to describe an instructional model for the endoscopic parasellar anatomy in sphenoid sinuses with ill-defined bony landmarks. Five preserved injected cadaveric heads and four sides of dry skulls were studied endoscopically via transethmoid, transsphenoidal approach. The parasellar region was exposed by drilling along the maxillary nerve (V2) canal [the length of the foramen rotundum (FR) between the middle cranial fossa and the pterygopalatine fossa]. This was achieved by drilling in the inferior part of the lateral wall of posterior ethmoids immediately above the sphenopalatine foramen. Cavernous V2 was traced to the paraclival internal carotid artery (ICA). Cavernous sinus (CS) apex was exposed by drilling a triangle bounded by V2 and its canal inferiorly, bone between FR and superior orbital fissure (SOF) anteriorly, and ophthalmic nerve (V1) superiorly. Drilling was continued toward the annulus of Zinn (AZ) and optic nerve superiorly and over the intracavernous ICA posteriorly. Endoscopic measurements between V2, SOF, AZ, and opticocarotid recess were obtained. Endoscopic systematic orientation of parasellar anatomy is presented that can be helpful for approaching sphenoid sinus with ill-defined bony landmarks.